Does PAD and microcirculation status impact the tissue availability of intravenously administered antibiotics in patients with infected diabetic foot? Results of the DFIATIM substudy - Fejfarová, Vladimíra; Jarošíková, Radka; Antalová, Simona; Husáková, Jitka; Wosková, Veronika; Beca, Pavol; Mrázek, Jakub; Tůma, Petr; Polák, Jan; Dubský, Michal; Sojáková, Dominika; Lánská, Věra; et al. (Frontiers in Endocrinology, 2024)
Aims/hypothesis The aim of this substudy (Eudra CT No:2019-001997-27)was to assess ATB availability in patients with infected diabetic foot ulcers(IDFUs)in the context of microcirculation and macrocirculation status. Methods For this substudy, we enrolled 23 patients with IDFU. Patients were treated with boluses of amoxicillin/clavulanic acid(AMC)(12patients) or ceftazidime(CTZ)(11patients). After induction of a steady ATB state, microdialysis was performed near the IDFU. Tissue fluid samples from the foot and blood samples from peripheral blood were taken within 6 hours. ATB potential efficacy was assessed by evaluating the maximum serum and tissue ATB concentrations(Cmax and Cmax-tissue)and the percentage of time the unbound drug tissue concentration exceeds the minimum inhibitory concentration (MIC)(≥100% tissue and ≥50%/60% tissue fT>MIC). Vascular status was assessed by triplex ultrasound, ankle–brachial and toe–brachial index tests, occlusive plethysmography comprising two arterial flow phases, and transcutaneous oxygen pressure(TcPO2). Results Following bolus administration, the Cmax of AMC was 91.8 ± 52.5 μgmL-1 and the Cmax-tissue of AMC was 7.25 ± 4.5 μgmL-1(P<0.001). The Cmax for CTZ was 186.8 ± 44.1 μgmL-1 and the Cmax-tissue of CTZ was 18.6 ± 7.4 μgmL-1(P<0.0001). Additionally, 67% of patients treated with AMC and 55% of those treated with CTZ achieved tissue fT>MIC levels exceeding 50% and 60%, respectively. We observed positive correlations between both Cmax-tissue and AUCtissue and arterial flow. Specifically, the correlation coefficient for the first phase was r=0.42; (P=0.045), and for the second phase, it was r=0.55(P=0.01)and r=0.5(P=0.021). Conclusions Bactericidal activity proved satisfactory in only half to two-thirds of patients with IDFUs, an outcome that appears to correlate primarily with arterial flow.